(untitled) (Baghdad Science Journal, 2019)
Seasonal variations of the species composition and abundance of Cladocera were studied in two stations at the end of the Tigris River and one station at the confluence of the Tigris with Euphrates area, at the beginning of the Shatt Al-Arab River in Al-Qurnah North of Basrah Province, from October 2015 to August 2016. Samples of zooplankton were collected by plankton net 100-µm. mesh size. The population density of Cladocera ranged between 1 Ind /m³ during summer and 211 Ind./m³ during winter at station 1 (Al-Jewaber Bridge). A total of 16 species of Cladocera belonging to 12 genera were recorded in the study. The average density of Cladocera ranged from 23.2 ind./m3 at Station 2 (Hamayon Bridge) to 53.7 Ind./m3 at Station 1 (Al-Jewaber Bridge). The results showed that the Bosmina meridionalis was dominant at the three stations 47.8%, while the other species were as follow Moina affinis 15.1%, Daphnia lumholtzi 9.3%, Simocephalus (Simocephalus) vetuloides 8.1% and Daphnia exilis 6.6% of the total Cladocera.